DIAGNOSIS OF MYOCARDIAL ISCHEMIA USING PLASMA FREE FATTY ACID AS A BIOMARKER - K, PRABHAVATHI; RV, HEMAMALINI; G, JAISRI; A, SARAVANAN (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Diagnosis of myocardial ischemia (MI) in patients attending emergency intensive care unit (ICU) with symptoms of an acute coronary disease is often difficult. Biochemical markers such as cardiac troponin (cTn) and creatinine kinase MB (CK-MB) may not rise during reversible MI. Previous studies suggest unbound free fatty acid (FFA) increased significantly in ischemic related events. Thus, plasma FFA has shown to be an early biochemical marker. To diagnose MI using plasma FFA as a biomarker. Methods: Blood samples were collected from 30 ischemic heart disease (IHD) patients admitted to ICU and 30 healthy volunteers for plasma FFA. Patients were diagnosed as IHD based on the clinical presentation, electrocardiogram (ECG), and coronary angiography findings, cTn, CK-MB. Plasma FFA was measured enzymatically with (acyl-CoA synthetase- acyl-CoA oxidase) non-esterified fatty acid kit (Randox Laboratories Ltd., Co.Antrium, United Kingdom) on Bayer RA 50 analyzer in both normals and IHD patients. Results: Around 93.3% of the patients presented with the chest pain as a major symptom and 6.7% of the patient presented with dyspnea. All the patients showed a positive ECG change and angiographic findings suggestive of IHD. Plasma FFA (1.134Â±0.21) in IHD was significantly higher (p<0.0001) than the control (0.5233Â±0.13). With respect to lipid profile triglycerides, low-density lipoprotein (LDL), very LDL was significantly higher in MI when compared to normal with p<0.001, whereas HDL was significantly higher in normals than the study group with p<0.05. There was no statistical difference in total cholesterol and hemoglobin value between the study group and the normals. Further standard biomarker like cTn was elevated in 60% (18) and CK-MB in 63% (19) of the patients when compared to FFA, which was elevated in 86% (26) of the patients. Conclusion: Thus, plasma FFA can be used as a simple, quick, and early marker of MI. However, should FFAs be measured routinely as a standard diagnostic marker of ischemia still warrants further studies? Keywords: Myocardial ischemia, plasma FFA, cardiac troponin, creatinine kinase MB